UM ESTUDO DE IDEOLOGIA – EDUCAÇÃO CIDADÃ: UMA ANÁLISE SOBRE AS MOTIVAÇÕES E ASPIRAÇÕES DOS ALUNOS DA ONG EDUCAFRO - Valeriano, Sandra Maria dos Santos (2006)
This study aimed to know, discuss and analyse the motivations and aspirations from poor as well as afro-descendant students who are taking the “pré- vestibular” courses at the Non-Governamental Organization EDUCAFRO, their entrance at universities and in the work market taking into account the inclusion and exclusion mechanisms of the Brazilian Educational System. Among many relevant studies about afro-descendants in the educational system, we would like to emphasize two of them that deal with social movements, education and citizenship. The first one is the dissertation thesis by Alexandre do Nascimento who presented it at UERJ Universidade do Estado do Rio de Janeiro, in 1999 called: Um Estudo sobre os Cursos Pré-Vestibulares Populares and the other one, also a dissertation thesis, is Anti-Racismo e Educação: O Projeto Político- Pedagógico das Lideranças Negras de Uberlândia em 2000”. This work was presented by Cristiane Maria Ribeiro. Reading these two works was crucial for this present thesis once both of them discuss the social debt that Brazil has to the afro-descendants in the educational system. We also emphasize the work of the afro-american professor, writer and activist for the human rights John Hope Franklin who states that compensatory politics have been applied since the 1960’s. These politics focused on offering the afro-americans the chance to take part in the social changes. Therefore, universities were obliged to implant quota politics and also procedures that were favaroble to the afro-american population. In Brazil, this struggle is being articulated by the Non-Governamental Organization EDUCAFRO that has been developing mechanisms of social inclusion justifying them by stating that they are a way to compensate the afro-brazilians for the discrimination suffered in the past. This would, EDUCAFRO argues, benefit in some sense a percentage of the brazilian population. During our bibliographical research we have found, in many of the works we have read, a great concern by the authors with the issue of Affirmative Action as a path to compensate the afro population despite the resistence from those who fear the social progress of the afro-descendants. Even so, recent researches indicate paths to revert this negative picture. Facing this reality, we have the challenge: what